2018
DOI: 10.1002/admt.201800318
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Graphene/PEDOT:PSS Microelectrodes for Electro‐ and Optophysiology

Abstract: Conventional opaque electrodes in microelectrode array (MEA) technology obstruct the view of cells in their immediate vicinity (e.g., ≈50 µm) from which the strongest extracellular action potentials are recorded. This limitation has been overcome by transparent graphene electrodes which allow for optical access essential for novel applications such as optogenetics and calcium imaging. Downscaling, necessary for high resolution single‐unit electrophysiological recordings, has been a significant challenge due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 30 publications
(35 reference statements)
1
33
0
Order By: Relevance
“…A similar dependence of surface impedance to the thickness of the electrode material was already shown by Kshirsagar et al [3] who demonstrated that increasing the PEDOT:PSS layer thickness (electrodeposited by different time durations) led to a decrease of the impedance value. As a comparison, the impedance of a PEDOT:PSS layer electrodeposited during 0.2 sec is around 700 kΩ whilst those of PEDOT:PSS layers electrodeposited during 10 sec is around 50 kΩ-the thickness of the PEDOT:PSS layer is proportional to the deposition time [3].…”
Section: Influence Of Pedot:pss Thicknesssupporting
confidence: 80%
See 3 more Smart Citations
“…A similar dependence of surface impedance to the thickness of the electrode material was already shown by Kshirsagar et al [3] who demonstrated that increasing the PEDOT:PSS layer thickness (electrodeposited by different time durations) led to a decrease of the impedance value. As a comparison, the impedance of a PEDOT:PSS layer electrodeposited during 0.2 sec is around 700 kΩ whilst those of PEDOT:PSS layers electrodeposited during 10 sec is around 50 kΩ-the thickness of the PEDOT:PSS layer is proportional to the deposition time [3].…”
Section: Influence Of Pedot:pss Thicknesssupporting
confidence: 80%
“…As a comparison, a transparency of 84% was obtained for graphene/PEDOT:PSS-based MEAbut with higher surface impedance value of 117.3 ± 9.2 MΩ µm 2 at 1 kHz (30 μm diameter) [3] while an 80% transparency was obtained using ITO-based MEAs [26] with a surface impedance value of 1250 MΩ µm 2 (80 μm diameter) [9]. Table 1 and Fig.…”
Section: Transmission Measurementmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition to gold nanomesh, PEDOT:PSS coating can effectively improve the electrochemical performance of other transparent MEAs such as graphene. [ 261 ] Recently we demonstrated that covering the open spaces between interconnected metal grid transparent microelectrodes with ITO could significantly increase the effective ESA without changing GSA. [ 262 ] The resulting microelectrodes exhibit improved electrochemical impedance (5.4–18.4 Ω cm 2 ) than both metal grid and ITO references, high optical transparency (59–81%), and superior mechanical flexibility with no changes in electrical performance after 5000 bendings against a small radius at 5 mm.…”
Section: Multimodal Microsystemsmentioning
confidence: 99%